GAMES OF INDIGENOUS PEOPLES: THE BODY PRACTICES (Fiep Bulletin - online, 2013)
This paper aims to present the body practices demonstrated in the Indigenous Games since its inception in 1996 until its last issue in 2011. Rocha Ferreira et. al. (2008, p. 47) states: "Indigenous Games in the city represent new ways to celebrate, to play, to overcome obstacles, to overcome without the intense competitiveness that often observed in the sport." The authors also include saying "The events of the games are indigenous urban achievements. A field where different knowledge and gather ancestors and contemporary socio-cultural meanings "(ibid., p. 47). The Games of Indigenous Peoples actions are idealized by national leaders, brothers Marcos and Carlos in partnership with the Ministry of Sports. The recognition of the Games is present in Article 217 of the Brazilian Constitution of 1988, which claims to be the duty of the State to protect, recover, register and publicize cultural events that bind sporty character to our ethno-historical roots. The body practices regarded by the natives as "traditional" - those that are part of their rituals and "Western" - like football games present on Indigenous Peoples interact to demonstrate the cultural manifestations of these people, with the intention of celebrating the meeting of ethnicities without worrying about results or performances. This set of practices are not demonstrated in all editions of JPIs, which corresponds only to those already presented, some of which accompanied the Games since its inception as the launch Archery, Running with logs or Huka Huka Fight. To the creators of these games every edition is necessary the presence of new bodily practices, enabling different ethnicities present what is done in the village, their cultural practices, so that other indigenous and non-indigenous may have knowledge.
Keywords: Indigenous games; body practices; tradition.